How can robots facilitate physical, cognitive, and social engagement in skilled nursing facilities? - Preston, Rhian C.; Shippy, Madison R.; Aldwin, Carolyn M.; Fitter, Naomi T. (Frontiers in Aging, 2024)
As people live longer, the population of older adults in need of support continues to expand relative to the available workforce of caregivers, necessitating new solutions to supplement caregiver availability for the physical, cognitive, and social needs of older adults. Robotics and automation present strong possible solutions. Past solutions have typically supported short-term rehabilitation and aging in place, yet many older adults live in skilled nursing facilities (SNFs), a setting reached by relatively little research to date. In this paper, we examine the unique needs of staff and residents at SNFs, after which we begin an iterative design process of robot-mediated wellness activities for the SNF space. We worked closely with domain experts in exercise science and physical therapy for older adults and a local SNF to design and test a series of robot-mediated activity prototypes with residents, visitors, and staff. We found that while both residents and staff highly value physical activity, there are nuanced challenges associated with supporting resident activity (one important element of overall wellbeing). As a result, we considered and tested a wide range of intervention options from usual approaches (e.g., mirroring movements) to creative approaches (e.g., social engagement via lewd humor). Our final design insights can inform practitioners who wish to use robots to support resident wellbeing in SNFs.